Development and assessment of gastroretentive sustained release captopril tablets - Mukozhiwa, Samantha Yolanda (Rhodes University, Faculty of Pharmacy, Pharmacy)
Cardiovascular diseases (CVD) are the leading cause of death worldwide and global projections predict that the number of deaths due to CVD will continue to increase over the next 17 years [1]. With the growing burden of CVD the design and development of formulations that optimise the delivery of existing therapeutic molecules may be an approach to improving the management of patients with CVD. Captopril (CPT) is an angiotensin converting enzyme (ACE) inhibitor used for the routine management of hypertension, cardiac failure and diabetic nephropathy [2-4]. However it has a relatively short half-life and typical therapeutic dosing regimens require multiple dosing [2]. CPT is a potential candidate for sustained oral drug delivery, however its poor stability profile and high water solubility present significant formulation challenges. CPT exhibits optimal stability at pH < 4 and is unstable in the alkaline environment of intestinal fluids [5]. A sustained release gastroretentive formulation is therefore proposed as an approach that may improve the in vivo stability of CPT in addition to slowly releasing the molecule at a desired rate that may also minimize the occurrence of drug-related adverse effects. A Capillary Zone Electrophoresis (CZE) method for the quantitation of CPT in pharmaceutical dosage forms was developed and optimised using a Central Composite Design (CCD) approach. The CZE method was found to have the necessary linearity, accuracy, precision, sensitivity and specificity for the analysis of CPT in pharmaceutical formulations. Preformulation studies were conducted as part of the preparative work required to manufacture high quality, stable gastroretentive sustained release CPT tablets. The experiments conducted were tailored for the development of CPT sustained release tablets using direct compression manufacture and included an analysis of particle size and shape, powder flow properties and CPT-excipient compatibility studies. The results revealed that there was no definite evidence of interactions between CPT and the excipients to be used to manufacture CPT tablets, and CPT formulations were developed using these excipients. A direct compression procedure was selected for tablet manufacture due to apparent simplicity and to avoid unnecessary exposure of CPT to the heat and moisture that would be encountered if a wet granulation manufacturing process was used. A numerical optimisation approach was used to predict a formulation composition that would produce minimal CPT release initially, a short floating lag time (FLT) and maximum CPT release after 12 hours of dissolution testing. The effect of increasing the agitation speed of USP Apparatus 2 on the release of CPT from the optimised formulation was also investigated. The results revealed that changing the speed of the paddle had only a relatively small impact on the in vitro release behaviour of CPT from the tablets. The optimised formulation was subjected to additional testing in an attempt to investigate the effects of pH and osmolarity on the swelling and erosion characteristics of the dosage form. It was important to evaluate the effects of pH and osmolarity from the perspective of the solubility and stability of CPT. The results generated from swelling studies revealed that the swelling characteristics of the proposed formulation were not significantly altered by a change in pH and osmolarity of the test medium and this is probably due to the non-ionic nature of HPMC. In addition, the results revealed that the solubility and/or stability of CPT in different dissolution media did not affect the water uptake and swelling of the tablet matrices. The results revealed the erosion rate constants were low and suggest that although polymer erosion does occur, the role of this phenomenon in the release of CPT may not be as significant as that of diffusion. The release kinetics of CPT from the tablets was established by fitting in vitro release data to several mathematical models. The in vitro release data were best described using the Korsmeyer-Peppas model and values of release exponent (n) suggest that the majority of the tablets exhibited an anomalous CPT transport mechanism. The short-term stability of the optimised formulation was established by undertaking stability studies at 25Â°/60% RH and 40Â°/75% RH. The results revealed that there was no significant change in appearance and physicochemical properties of the tablets over 60 days. In conclusion, gastroretentive sustained release CPT tablets with the potential for further development and optimisation have been successfully developed and assessed in these studies. A basis is thus provided for further development of this technology.
Keywords: Captopril; Drug delivery systems; Drugs -- Controlled release; Cardiovascular system -- Diseases; Cardiovascular agents; Angiotensin converting enzyme; Inhibitors